UJI AKTIVITAS TABIR SURYA EKSTRAK ETANOL TUMBUHAN SEMBUNG RAMBAT (Mikania micrantha Kunth) SECARA IN VITRO - Susi lestari -; emma susanti (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id)
Sembung rambat (Mikania micrantha Kunth) is one of the plants that contain flavonoid compound. The flavonoid have the potential as a sunscreen, because it have chromophores group which can abssorption (UV A) dan (UV B) rays). The purpose of this research was to know the concentration of extract potentially as sunscreen and determine the value of SPF (Sun Protection Factor) , so it can be continued into natural sunscreen preparation. The sunscreen activity test method was performed in vitro using a UV-VIS spectrophotometer. Sunscreen activity test done by calculating the percent value of erytema transmission (% Te) and percent value of pigmentation transmission (% Tp) and SPF value. The results of the calculation of percentage value of erytema transmission (% Te) and sunscreen category at concentration 100, 150, 200 dan 250 ppm were 11,3024 % (standard suntan); 3,5238 % (extra protection); 1,3865 % (extra protection) dan 0,3838 % (sunblock). The calculation of percentage value of pigmentation transmission (% Tp) and sunscreen category at concentration 100, 150, 200 dan 250 ppm were 11,0254; 3,7011; 1,7447 and 0,5462 % all with the sunblock category. The SPF value at 250 ppm was 42,8810 with high protection category. The concentration was potentially developed into a natural sunscreen preparation that is at a concentration of 250 ppm.